2021
DOI: 10.7759/cureus.12428
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Thoracolumbar Injury Classification in the Clinical Outcome of Operative and Non-Operative Treatments

Abstract: This review assesses the validity of a biomechanical approach using finite element analysis in the Thoracolumbar Injury Classification and Severity Score System (TLICS) by addressing the “gray zone” decision discrepancy of thoracolumbar spinal injuries. A systematic review was performed using the keywords “Thoracolumbar Injury Classification” AND “finite element analysis of the spinal column” to evaluate the validity of the TLICS and finite element analysis of the thoracolumbar spinal column. Results were clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 26 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…Postoperative complications: Regards to postoperative complications, CSF leakage occurs in only one patient of short segment fixation group (3.3%) versus two patients of long segment fixation group (6.7%), also new neurological deficit occurs in only two patients of short segment fixation group (6.7%) versus three patients of long segment fixation group (10%) of insignificant difference between two studied groups (p=0.571). A 10-year follow-up study by Toyone et al [18] suggested that the benefit of short-segment fixation for burst fractures involving neurological deficit is that it can preserve thoracolumbar motion without resulting in post-traumatic disc degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative complications: Regards to postoperative complications, CSF leakage occurs in only one patient of short segment fixation group (3.3%) versus two patients of long segment fixation group (6.7%), also new neurological deficit occurs in only two patients of short segment fixation group (6.7%) versus three patients of long segment fixation group (10%) of insignificant difference between two studied groups (p=0.571). A 10-year follow-up study by Toyone et al [18] suggested that the benefit of short-segment fixation for burst fractures involving neurological deficit is that it can preserve thoracolumbar motion without resulting in post-traumatic disc degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Posterior Ligamentous Complex (PLC) integrity 3. Patient's neurological status TLICS relies on X-ray, CT and magnetic resonance imaging (MRI) and provides a management algorithm (Table 1) that still requires the experienced judgement of spine surgeons to make a decision in many cases [11,12]. TLICS fails to consider the vitally important patient-specific modifiers in tailoring the management plan to individual patients [10,13].…”
Section: Timeline Of Classification Systemsmentioning
confidence: 99%
“…While operative treatment is typically preferred for severe fractures with posterior ligamentous complex injury or neurological deficit, nonoperative treatment is usually preferred for minor fractures with minimal bone injuries [4]. However, the TLICS system has a major drawback when it comes to deciding the treatment for patients with TLICS 4 fracture [6][7][8]. The best treatment for thoracolumbar fracture patients with moderate injury of TLICS 4 remains the surgeon's choice [9,10].…”
Section: Introductionmentioning
confidence: 99%